Mast cells: a double-edged sword in inflammation and fibrosis - Wang, Xufang; Zhang, Peipei; Tang, Yuxin; Chen, Yanlin; Zhou, Enchao; Gao, Kun (Frontiers in Cell and Developmental Biology, 2024)
As one of the key components of the immune system, mast cells are well known for their role in allergic reactions. However, they are also involved in inflammatory and fibrotic processes. Mast cells participant in all the stages of acute inflammatory responses, playing an immunomodulatory role in both innate immunity and adaptive immunity. Mast cell derived histamine, TNF-α and IL-6 contribute to the inflammatory processes, while IL-10 mediates the suppression of inflammation. Crosstalk between mast cells and other immune cells are also involved in the development of inflammation. The cell-cell adhesion of mast cells and fibroblasts is crucial for fibrosis. Mast cell mediators including cytokines and proteases play contradictory role in fibrotic process. Here, we review the double-edged role of mast cells in inflammation and fibrosis.